ДИСНЕЙРООНТОГЕНЕТИЧНІ ДЕТЕРМІНАНТИ ПОРУШЕНЬ КОМУНІКАТИВНО-МОВЛЕННЄВОЇ ДІЯЛЬНОСТІ У ДІТЕЙ ДОШКІЛЬНОГО ВІКУ НА ЕТАПІ АНТЕНАТАЛЬНОГО РОЗВИТКУ - Наталія Лопатинська (World Science, 2019)
The article is devoted to the study of the influence of dysontogenetic determinants (factors) of antenatal period on the formation and development of communicative and speech activity of a preschool child with different types of linguistic dysontogenesis. To achieve the purpose of the article, the following methods were used: theoretical (comparison, generalization and systematization of the results of diagnostic researches), empirical (diagnostic: standardized interviews, questionnaires, tests, analysis of medical documentation; observational: direct and indirect monitoring, protocoling); statistical (the establishment of the discrepancy with Fisher's multifunctional statistical criterion (Fisher's angular transformation)). Disneurotonogenetic determination of the main causes of communicative and speech activity disorders in preschool children predetermines the practicability of the development of a neurological correction individual trajectory and abilitional programs to reduce and minimize the manifestations of disorders in communicative and speech activity in children belonging to the group of biological and social risk.